Economic Evaluation of Dupilumab for the Treatment of Moderate-to-Severe Atopic Dermatitis in Adults - Kuznik, Andreas (Dermatol Ther (Heidelb), 2017)
INTRODUCTION: Dupilumab significantly improves signs and symptoms of atopic dermatitis (AD), including pruritus, symptoms of anxiety and depression, and health-related quality of life versus placebo in adults with moderate-to-severe AD. Since the cost-effectiveness of dupilumab has not been evaluated, the objective of this analysis was to estimate a value-based price range in which dupilumab would be considered cost-effective compared with supportive care (SC) for treatment of moderate-to-severe AD in an adult population. METHODS: A health economic model was developed to evaluate from the US payer perspective the long-term costs and benefits of dupilumab treatment administered every other week (q2w). Dupilumab q2w was compared with SC; robustness of assumptions and results were tested using sensitivity and scenario analyses. Clinical data were derived from the dupilumab LIBERTY AD SOLO trials; healthcare use and cost data were from health insurance claims histories of adult patients with AD. The annual price of maintenance therapy with dupilumab to be considered cost-effective was estimated for decision thresholds of US$100,000 and $150,000 per quality-adjusted life-year (QALY) gained. RESULTS: In the base case, the annual maintenance price for dupilumab therapy to be considered cost-effective would be $28,770 at a $100,000 per QALY gained threshold, and $39,940 at a $150,000 threshold. Results were generally robust to parameter variations in one-way and probabilistic sensitivity analyses. CONCLUSION: Dupilumab q2w compared with SC is cost-effective for the treatment of moderate-to-severe AD in US adults at an annual price of maintenance therapy in the range of $29,000–$40,000 at the $100,000–$150,000 per QALY thresholds. FUNDING: Sanofi and Regeneron Pharmaceuticals, Inc.